2011
DOI: 10.1093/ndt/gfr491
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal, every-other-day, online haemodiafiltration: an effective therapeutic alternative

Abstract: Nocturnal every-other-day OL-HDF could be an excellent therapeutic alternative since good tolerance and occupational rehabilitation, marked improvement in dialysis dose, nutritional status, LVH, phosphate and hypertension control and a substantial reduction in drug requirements were observed. In this crossover study, different removal patterns of large solutes were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 39 publications
2
47
0
2
Order By: Relevance
“…It is unclear what value HDF could add to more frequent dialysis schedules. 13 Furthermore, published data on HDF in children are very limited. In this group of patients, a totally different endpoint, growth acceleration, could be of great relevance.…”
mentioning
confidence: 99%
“…It is unclear what value HDF could add to more frequent dialysis schedules. 13 Furthermore, published data on HDF in children are very limited. In this group of patients, a totally different endpoint, growth acceleration, could be of great relevance.…”
mentioning
confidence: 99%
“…These two approaches, HDF and extended treatment time, should not be considered competitive but rather complementary. Only a few studies have combined the solute mass transfer capacity of HDF with increased treatment time [19][20][21] and all clinical trials have confirmed the tremendous benefits of such combination on intermediary and long-term outcomes.…”
Section: Why Is Hemodiafiltration Needed?mentioning
confidence: 99%
“…This can be achieved by avoiding the two days weekend gap and implementation of in-center every other day dialysis [11,113]. A recent study of analyzing records of 32,000 people receiving dialysis three times a week from 2005 through 2008 found a 22% greater risk of death on the day after a long break, compared with other days.…”
Section: Frequent Hemodialysismentioning
confidence: 99%
“…Hyperphosphatemia, which has been associated with vascular calcification and considered as an independent predictor of mortality in dialysis patients [132], has been well controlled with efficient removal of phosphorus by online HDF [113,129,133] with marked reduction in phosphate binders [113]. Furthermore, the reduction ratio of β 2 -M per session has been shown to be 20-30% higher with online HDF than with high-flux HD (72.7 versus 49.7%) [134].…”
Section: Online Hemodiafiltrationmentioning
confidence: 99%
See 1 more Smart Citation